Resource Nationalism, Enclave Industrialization, and Regional Divergence: A Spatial Econometric Assessment of Indonesia's Hilirisasi Mandate - Iqbal Anugerah; Selma Fajic (HM Publisher, 2026)
Indonesia's hilirisasi (downstreaming) mandate, enforced through a definitive nickel mineral export ban from January 2020, represents one of the most consequential applications of resource nationalism in contemporary Southeast Asian political economy. While aggregate indicators documented substantial Foreign Direct Investment (FDI) inflows into metallurgical industrial parks, the sub-national distributional consequences remained critically underexplored prior to this study. Employing a Spatial Durbin Difference-in-Differences (SDM-DiD) framework applied to a balanced provincial panel of 34 Indonesian provinces across the period 2015 to 2024 (N = 340 observations), this study empirically decomposed the direct, indirect (spatial spillover), and total effects of the export ban on regional economic growth and income inequality. The treatment group comprised the three primary nickel-downstreaming hub provinces: Central Sulawesi, Southeast Sulawesi, and North Maluku. Moran's I statistics confirmed significant spatial autocorrelation across all study years (range: 0.245-0.312, p < 0.001), validating the spatial modeling approach. The SDM-DiD estimation revealed a significant positive direct effect on regional GDP per capita in treated provinces (beta = 0.084, SE = 0.019, p < 0.001), confirming localized growth. However, the spatial spillover effect was significantly negative (theta = -0.052, SE = 0.021, p = 0.013), documenting a pronounced backwash effect on adjacent provinces. Within treated regions, income inequality widened significantly (Gini direct effect: beta = 0.018, p < 0.001), driven by skill-biased structural transformation associated with capital-intensive smelting operations. These findings established that Indonesia's hilirisasi mandate functions structurally as an enclave industrialization model, generating spatial polarization rather than inclusive regional development. Inter-regional fiscal equalization, enforceable backward linkage obligations, and peripheral human capital investment are identified as critical complementary policy mechanisms.